Adverse Interactions of Luminescent Semiconductor Quantum Dots with Liposomes and Shewanella oneidensis - Williams, Denise N. (ACS Appl Nano Mater, 2018)
Cadmium-containing luminescent quantum dots (QD) are increasingly used in display, bioimaging, and energy technologies; however, significant concerns have been raised about their potentially adverse impact on human health and the environment. This study makes use of a broad toolkit of analytical methods to investigate and increase our understanding of the interactions of luminescent cadmium-containing (CdSe) and cadmium-free (ZnSe) QD, with and without a passivating higher bandgap energy ZnS shell, with phospholipid vesicles (liposomes), which model bacterial membranes, and with Shewanella oneidensis MR-1, an environmentally relevant bacteria. A unique feature of this study is that all QD types have the same surface chemistry, being capped with uncharged poly(ethylene glycol) ligands. This enables focusing the study on the impact of the QD core on liposomes and bacterial cells. The study reveals that QD association with liposome and bacterial cell membranes is imperative for their adverse impact on liposomes and bacterial cells. The QD’ concentration-dependent association with liposomes and bacterial cells destabilizes the membranes mechanically, which leads to membrane disruption and lysis in liposomes and to bacterial cell death. The study also shows that cadmium-containing QD exhibit a higher level of membrane disruption in bacterial cells than cadmium-free QD. ZnSe QD have low membrane impact, and coating them with a ZnS shell decreases their membrane disruption activity. In contrast, CdSe QD exhibit a high level of membrane impact, and coating them with a ZnS shell does not decrease, but in fact further increases, their membrane disruption activity. This behavior might be attributed to higher affinity and association of CdSe/ZnS QD with liposomes and bacterial cells and to a contribution of dissolved zinc ions from the ZnS shell to increased membrane disruption activity.